Effect of Social Capital on Smoking and Alcohol Consumption Behavior in Adults - Maoli Zartika; Bhisma Murti; Argyo Demartoto (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Clinical epidemiological studies show that smoking and alcohol are often used together as social activities. Smoking and alcohol consumption are related to the risk of developing non-communicable diseases. According to data from the Indonesian Health Survey (SKI), (2023) the percentage of smokers in Surakarta City is 23.6% and the percentage of alcohol consumption is 1.4%. This study aims to analyze the influence of social capital on smoking behavior and alcohol consumption in adults. Subjects and Method: The research design used is a cross-sectional study. The population in this study is adults aged 19-59 years in the city of Surakarta. Sampling in the study was carried out by the snowball sampling method, then as many as 200 adults domiciled in the city of Surakarta were obtained. The method used in collecting data for this study is a questionnaire. The analysis used in this study is the Structural Equation Model (SEM) to analyze the influence of social capital elements on smoking behavior and alcohol consumption in adults. The dependent variables are smoking habits and alcohol consumption. The independent variable is social capital including 3 elements, namely structural elements, cognitive elements and relational elements. Results: Social capital had a negative effect on smoking behavior (b= -0.80; 95% CI= -0.88 to -0.71; p= 0.001), and social capital has a negative effect on alcohol consumption (b= -0.71; 95% CI= -0.80 to -0.63; p= 0.001). Conclusion: The results of this study show that social capital constructs include structural elements, cognitive elements and relational elements that are high have a lower likelihood of smoking behavior and alcohol consumption in adults.